Use of industry 4.0 tools for prototyping in the clothing sector (DAPesquisa, 2021)
The digital technologies of Industry 4.0, bring benefits to the clothing companies, with the optimization of the processes, the speed of production and the connection between the machines, which allows the integration of the entire value chain. This article discusses the use of tools from industry 4.0 in the prototyping of clothing products. Basic research with theoretical foundations was applied, with a qualitative and descriptive approach. Data collection was carried out in books, scientific articles, theses and dissertations, bringing the principles and pillars of industry 4.0, as well as the tools that enable 3D (three-dimensional) prototyping of clothing products. The relevance of the research is highlighted, considering that the global analysis of the technical feasibility of the product, which assesses the layout of the modeling, the dressability, the ergonomic aspects and the trim of the pieces, are done in a virtual environment, thus dispensing: the plotting of the molds, selection and preparation of the fabric for cutting, tracing of the scratch and cutting of the molds and assembly (preparation and sewing) of the garment model pieces. The research results reveal that it is possible to be effective in the production and reduction of working time and sustainable benefits with the use of 3D prototyping tools for clothing products, in social, environmental and financial terms.
Keywords: Clothing and dress - Industry; Rapid prototyping; Three-dimensional modeling; Industry 4.0